Safety and Tolerability of Adipose-Derived Mesenchymal Stem Cell (ADR-001) Therapy for IgA Nephropathy - Akihito Tanaka; Kazuhiro Furuhashi; Kumiko Fujieda; Asuka Horinouchi; Kayaho Maeda; Shoji Saito; Tetsushi Mimura; Yosuke Saka; Tomohiko Naruse; Takuji Ishimoto; Noritoshi Kato; Tomoki Kosugi; et al. (Kidney360)
Key Points. IgA nephropathy often requires KRT. Mesenchymal stem cells offer clinical benefits. Adipose-derived mesenchymal stem cells are safe and tolerable. Background. IgA nephropathy (IgAN) often requires KRT because of its refractoriness and because corticosteroids pose infection risks. However, mesenchymal stem cells offer clinical benefits because of their regenerative and immunomodulatory properties. This prospective clinical trial assessed the safety and tolerability of adipose-derived mesenchymal stem cell (ASC) therapy and evaluated its therapeutic efficacy. Methods. This phase 1 study included adult patients with refractory IgAN that was difficult to treat with traditional therapies. ASC therapy comprising one intravenous dose of 1×108 cells was administered to three to six patients in Cohort 1. The same intravenous dose was administered twice with a 2-week interval to six patients in Cohort 2. Heparin was administered simultaneously. This study continued for 52 weeks, and the primary end points were safety and tolerability during the 6-week period after treatment administration. Secondary end points included adverse events and efficacy measures such as clinical remission, partial remission, urine protein remission, hematuria remission, time to remission, changes in the urine protein and hematuria levels, and changes in the eGFR. Results. The three patients in Cohort 1 and six patients in Cohort 2 who received ASC therapy achieved the primary end points. No severe adverse clinical events were observed. Therefore, the safety and tolerability of ASCs were confirmed. Improvements, such as significantly decreased kidney damage markers and urinary protein levels, were observed immediately after ASC administration. Conclusions. The safety and tolerability of ASCs are acceptable for patients with IgAN. Clinical Trial registry name and registration number:. This trial was registered with the Japan Registry of Clinical Trials (jRCT2043200002; registration date: April 14, 2020) and ClinicalTrials.gov (NCT04342325; registration date: April 13, 2020).